# Class 8 RD Sharma Solutions- Chapter 6 Algebraic Expressions And Identities – Exercise 6.6 | Set 1

**Question 1. Write the following squares of binomials as trinomials:**

**(i) (x + 2)**^{2}

^{2}

**Solution:**

x

^{2}+ 2 (x) (2) + 22Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.x

^{2}+ 4x + 4

**(ii) (8a + 3b)**^{2}

^{2}

**Solution:**

(8a)

^{2}+ 2 (8a) (3b) + (3b)64a

^{2}+ 48ab + 9b^{2}

**(iii) (2m + 1)**^{2}

^{2}

**Solution:**

(2m)

^{2}+ 2 (2m) (1) + 1^{2}4m

^{2}+ 4m + 1

**(iv) (9a + 1/6)**^{2}

^{2}

**Solution:**

(9a)

^{2}+ 2 (9a) (1/6) + (1/6)^{2}81a

^{2}+ 3a + 1/36

**(v) (x + x**^{2}/2)^{2}

^{2}/2)

^{2}

**Solution:**

(x)

^{2}+ 2 (x) (x^{2}/2) + (x^{2}/2)^{2}x

^{2}+ x^{3}+ 1/4x^{4}

**(vi) (x/4 – y/3)**^{2}

^{2}

**Solution:**

(x/4)

^{2}– 2 (x/4) (y/3) + (y/3)^{2}1/16x

^{2}– xy/6 + 1/9y^{2}

**(vii) (3x – 1/3x)**^{2}

^{2}

**Solution:**

(3x)

^{2}– 2 (3x) (1/3x) + (1/3x)^{2}9x

^{2}– 2 + 1/9x^{2}

### (**viii) (x/y – y/x)**^{2}

^{2}

**Solution:**

(x/y)

^{2 }– 2 (x/y) (y/x) + (y/x)^{2}x

^{2}/y^{2}– 2 + y^{2}/x^{2}

**(ix) (3a/2 – 5b/4)**^{2}

^{2}

**Solution:**

(3a/2)

^{2}– 2 (3a/2) (5b/4) + (5b/4)^{2}9/4a

^{2 }– 15/4ab + 25/16b^{2}

**(x) (a**^{2}b – bc^{2})^{2}

^{2}b – bc

^{2})

^{2}

**Solution:**

(a

^{2}b)^{2}– 2 (a^{2}b) (bc^{2}) + (bc^{2})^{2}a

^{4}b^{4}– 2a^{2}b^{2}c^{2}+ b^{2}c^{4}

**(xi) (2a/3b + 2b/3a)**^{2}

^{2}

**Solution:**

(2a/3b)

^{2}+ 2 (2a/3b) (2b/3a) + (2b/3a)^{2}4a

^{2}/9b^{2}+ 8/9 + 4b^{2}/9a^{2}

**(xii) (x**^{2} – ay)^{2}

^{2}– ay)

^{2}

**Solution:**

(x

^{2})^{2}– 2 (x^{2}) (ay) + (ay)^{2}x

^{4}– 2x^{2}ay + a^{2}y^{2}

**Question 2. Find the product of the following binomials:**

**i) (2x + y) (2x + y)**

**Solution:**

2x (2x + y) + y (2x + y)

4x

^{2}+ 2xy + 2xy + y^{2}4x

^{2}+ 4xy + y^{2}

**(ii) (a + 2b) (a – 2b)**

**Solution:**

a (a – 2b) + 2b (a – 2b)

a

^{2}– 2ab + 2ab – 4b^{2}a

^{2}– 4b^{2}

**(iii) (a**^{2} + bc) (a^{2} – bc)

^{2}+ bc) (a

^{2}– bc)

**Solution:**

a

^{2}(a^{2}– bc) + bc (a^{2}– bc)a

^{4}– a^{2}bc + bca^{2}– b^{2}c^{2}a

^{4}– b^{2}c^{2}

**(iv) (4x/5 – 3y/4) (4x/5 + 3y/4)**

**Solution:**

4x/5 (4x/5 + 3y/4) – 3y/4 (4x/5 + 3y/4)

16/25x

^{2}+ 12/20yx – 12/20xy – 9y^{2}/1616/25x

^{2}– 9/16y^{2}

**(v) (2x + 3/y) (2x – 3/y)**

**Solution:**

2x (2x – 3/y) + 3/y (2x – 3/y)

4x

^{2}– 6x/y + 6x/y – 9/y^{2}4x

^{2}– 9/y^{2}

**(vi) (2a**^{3} + b^{3}) (2a^{3} – b^{3})

^{3}+ b

^{3}) (2a

^{3}– b

^{3})

**Solution:**

2a

^{3}(2a^{3}– b^{3}) + b^{3}(2a^{3}– b^{3})4a

^{6}– 2a^{3}b^{3}+ 2a^{3}b^{3}– b^{6}4a

^{6}– b^{6}

**(vii) (x**^{4} + 2/x^{2}) (x^{4} – 2/x^{2})

^{4}+ 2/x

^{2}) (x

^{4}– 2/x

^{2})

**Solution:**

= x

^{4}(x^{4}– 2/x^{2}) + 2/x^{2}(x^{4}– 2/x^{2})= x

^{8}– 2x^{2}+ 2x^{2}– 4/x^{4}= (x

^{8}– 4/x^{4})

**(viii) (x**^{3} + 1/x^{3}) (x^{3} – 1/x^{3})

^{3}+ 1/x

^{3}) (x

^{3}– 1/x

^{3})

**Solution:**

= x

^{3}(x^{3}– 1/x^{3}) + 1/x^{3}(x^{3}– 1/x^{3})= x

^{6}– 1 + 1 – 1/x^{6}= x

^{6}– 1/x^{6}

**Question 3. Using the formula for squaring a binomial, evaluate the following:**

**(i) (102)**^{2}

^{2}

**Solution:**

We can rewrite 102 as 100 + 2

(102)2 = (100 + 2)2

By simplification ,

(100 + 2)2 = (100)2 + 2 (100) (2) + 22

= 10000 + 400 + 4 = 10404

**(ii) (99)**^{2}

^{2}

**Solution:**

We can rewrite 99 as 100 – 1

(99)

^{2}= (100 – 1)^{2}On simplification,

(100 – 1)

^{2}= (100)^{2}– 2 (100) (1) + 1^{2}= 10000 – 200 + 1 = = 9801

**(iii) (1001)**^{2}

^{2}

**Solution:**

We can rewrite 1001 as 1000 + 1

(1001)

^{2}= (1000 + 1)^{2}On simplification ,

(1000 + 1)

^{2}= (1000)^{2}+ 2 (1000) (1) + 1^{2}= 1000000 + 2000 + 1 = 1002001

**(iv) (999)**^{2}

^{2}

**Solution:**

We can rewrite 999 as 1000 – 1

(999)

^{2}= (1000 – 1)^{2}By simplification,

(1000 – 1)

^{2}= (1000)2 – 2 (1000) (1) + 12= 1000000 – 2000 + 1 = 998001

**(v) (703)**^{2}

^{2}

**Solution:**

We can rewrite 700 as 700 + 3

(703)

^{2}= (700 + 3)^{2}By simplification,

(700 + 3)2 = (700)2 + 2 (700) (3) + 32

= 490000 + 4200 + 9 = 494209

**Question 4. Simplify the following using the formula: (a – b) (a + b) = a**^{2} – b^{2} :

^{2}– b

^{2}:

**(i) (82)**^{2} – (18)^{2}

^{2}– (18)

^{2}

**Solution:**

Here we will use the formula

(82)

^{2}– (18)^{2}= (82 – 18) (82 + 18)= 64 × 100

= 6400

**(ii) (467)**^{2} – (33)2^{2}

^{2}– (33)2

^{2}

**Solution:**

We will using the formula (a – b) (a + b) = a

^{2}– b^{2}(467)

^{2}– (33)^{2}= (467 – 33) (467 + 33)= (434) (500)

= 217000

**(iii) (79)**^{2} – (69)^{2}

^{2}– (69)

^{2}

**Solution:**

We will using the formula (a – b) (a + b) = a

^{2}– b^{2}(79)

^{2}– (69)^{2}= (79 + 69) (79 – 69)= (148) (10)

= 1480

**(iv) 197 × 203**

**Solution:**

We can rewrite 203 as 200 + 3 and 197 as 200 – 3

We will using the formula (a – b) (a + b) = a

^{2}– b^{2}197 × 203 = (200 – 3) (200 + 3)

= (200)

^{2}– (3)^{2}= 40000 – 9

= 39991

**(v) 113 × 87**

**Solution:**

We can rewrite 113 as 100 + 13 and 87 as 100 – 13

We can using the formula (a – b) (a + b) = a

^{2}– b^{2}113 × 87 = (100 – 13) (100 + 13)

= (100)

^{2}– (13)^{2}= 10000 – 169

= 9831

**(vi) 95 × 105**

**Solution:**

We can rewrite 95 as 100 – 5 and 105 as 100 + 5

We will using the formula (a – b) (a + b) = a

^{2}– b^{2}95 × 105 = (100 – 5) (100 + 5)

= (100)

^{2}– (5)^{2}= 10000 – 25

= 9975

**(vii) 1.8 × 2.2**

**Solution:**

We can rewrite 1.8 as 2 – 0.2 and 2.2 as 2 + 0.2

We will using the formula (a – b) (a + b) = a

^{2}– b^{2}1.8 × 2.2 = (2 – 0.2) ( 2 + 0.2)

= (2)

^{2}– (0.2)^{2}= 4 – 0.04

= 3.96

**(viii) 9.8 × 10.2**

**Solution:**

We can rewrite 9.8 as 10 – 0.2 and 10.2 as 10 + 0.2

We will using the formula (a – b) (a + b) = a

^{2}– b^{2}9.8 × 10.2 = (10 – 0.2) (10 + 0.2)

= (10)

^{2}– (0.2)^{2}= 100 – 0.04

= 99.96

**Question 5. Simplify the following using the identities:**

**(i) ((58)**^{2} – (42)^{2})/16

^{2}– (42)

^{2})/16

**Solution:**

We will using the formula (a – b) (a + b) = a

^{2}– b^{2}((58)

^{2}– (42)^{2})/16 = ((58-42) (58+42)/16)= ((16) (100)/16)

= 100

**(ii) 178 × 178 – 22 × 22**

**Solution:**

We will using the formula (a – b) (a + b) = a

^{2}– b^{2}178 × 178 – 22 × 22 = (178)

^{2}– (22)^{2}= (178-22) (178+22)

= 200 × 156

= 31200

**(iii) (198 × 198 – 102 × 102)/96**

**Solution:**

We using the formula (a – b) (a + b) = a

^{2}– b^{2}(198 × 198 – 102 × 102)/96 = ((198)2 – (102)2)/96

= ((198-102) (198+102))/96

= (96 × 300)/96

= 300

**(iv) 1.73 × 1.73 – 0.27 × 0.27**

**Solution:**

We will using the formula (a – b) (a + b) = a

^{2}– b^{2}1.73 × 1.73 – 0.27 × 0.27 = (1.73)2 – (0.27)2

= (1.73-0.27) (1.73+0.27)

= 1.46 × 2

= 2.92

**(v) (8.63 × 8.63 – 1.37 × 1.37)/0.726**

**Solution:**

We will using the formula (a – b) (a + b) = a

^{2}– b^{2}(8.63 × 8.63 – 1.37 × 1.37)/0.726 = ((8.63)2 – (1.37)2)/0.726

= ((8.63-1.37) (8.63+1.37))/0.726

= (7.26 × 10)/0.726

= 72.6/0.726

= 100

**Question 6. Find the value of x, if:**

**(i) 4x = (52)**^{2} – (48)^{2}

^{2}– (48)

^{2}

**Solution:**

We will using the formula (a – b) (a + b) = a

^{2}– b^{2}4x = (52)

^{2}– (48)^{2}4x = (52 – 48) (52 + 48)

4x = 4 × 100

4x = 400

x = 100

**(ii) 14x = (47)**^{2} – (33)^{2}

^{2}– (33)

^{2}

**Solution:**

We will using the formula (a – b) (a + b) = a2 – b2

14x = (47)2 – (33)2

14x = (47 – 33) (47 + 33)

14x = 14 × 80

x = 80

**(iii) 5x = (50)**^{2} – (40)^{2}

^{2}– (40)

^{2}

**Solution:**

We using the formula (a – b) (a + b) = a2 – b2

5x = (50)

^{2}– (40)^{2}5x = (50 – 40) (50 + 40)

5x = 10 × 90

5x = 900

x = 180

**Question 7. If x + 1/x =20, find the value of x**^{2} + 1/ x^{2}.

^{2}+ 1/ x

^{2}.

**Solution:**

Given equation in the x + 1/x = 20

when squaring both sides, we get

(x + 1/x)

^{2}= (20)^{2}x

^{2}+ 2 × x × 1/x + (1/x)^{2}= 400x

^{2}+ 2 + 1/x^{2}= 400x

^{2}+ 1/x^{2}= 398

**Question 8. If x – 1/x = 3, find the values of x**^{2} + 1/ x^{2} and x^{4} + 1/ x^{4}.

^{2}+ 1/ x

^{2}and x

^{4}+ 1/ x

^{4}.

**Solution:**

Given in the question x – 1/x = 3

when squaring both sides,

(x – 1/x)

^{2}= (3)^{2}x

^{2}– 2 × x × 1/x + (1/x)^{2}= 9x

^{2}– 2 + 1/x^{2}= 9x

^{2}+ 1/x^{2}= 9+2x

^{2}+ 1/x^{2}= 11Now again when we square on both sides ,

(x

^{2}+ 1/x^{2})^{2}= (11)^{2}x

^{4}+ 2 × x^{2}× 1/x^{2}+ (1/x^{2})^{2}= 121x

^{4 }+ 2 + 1/x^{4}= 121x

^{4}+ 1/x^{4}= 121-2x

^{4 }+ 1/x^{4}= 119x

^{2}+ 1/x^{2}= 11x

^{4}+ 1/x^{4}= 119

**Question 9. If x**^{2} + 1/x^{2} = 18, find the values of x + 1/ x and x – 1/ x.

^{2}+ 1/x

^{2}= 18, find the values of x + 1/ x and x – 1/ x.

**Solution:**

Given in the question x

^{2}+ 1/x^{2}= 18When adding 2 on both sides,

x

^{2}+ 1/x^{2}+ 2 = 18 + 2x

^{2}+ 1/x^{2}+ 2 × x × 1/x = 20(x + 1/x)

^{2}= 20x + 1/x = √20

When subtracting 2 from both sides,

x

^{2}+ 1/x^{2}– 2 × x × 1/x = 18 – 2(x – 1/x)

^{2}= 16x – 1/x = √16

x – 1/x = 4

**Question 10. If x + y = 4 and xy = 2, find the value of x**^{2} + y^{2}

^{2}+ y

^{2}

**Solution:**

We know that x + y = 4 and xy = 2

Upon squaring on both sides of the given expression, we get

(x + y)

^{2}= 42x

^{2}+ y^{2}+ 2xy = 16x

^{2}+ y^{2}+ 2 (2) = 16 (since x y=2)x

^{2}+ y^{2}+ 4 = 16x

^{2}+ y^{2}= 16 – 4x

^{2}+ y^{2}=12